Exploring perceptions of psychology students in Delhi-NCR Region towards using mental health apps to promote resilience: a qualitative study - Shreya Chawla; Sneha Saha (BMC, 2024)
Abstract Background Mental health apps (MHapps) have the potential to become an essential constituent for addressing mental health disparities and influencing the psychological outcomes of students in India. Though lauded as a practical approach to preventing various mental health issues, there are concerns that developing and utilizing MHapps standardized on Western populations produce ineffective results for the natives of Asian countries such as India due to a wide range of cultural differences. This research was conducted on psychology students living in the Delhi-NCR region of the Indian subcontinent. The study explored psychology students' perceptions, needs, and preferences regarding mental health apps that promote resilience, identified barriers and facilitators for developing effective mental health apps, and explored the cultural relevance of the development of MHapps in India. Methods This was an exploratory study utilizing focus group discussions among psychology students. Psychology students were sampled using snowball sampling from Delhi-NCR region colleges to participate in FGDs. We conducted six focus groups, which included a representation of 30 psychology students from full-time UG/PG courses. The study used a reflexive thematic analysis framework using the six-step Braun and Clarke process to develop themes. Results Psychology students valued MHapps for their easy accessibility, 24*7 functionality, affordable costs, highly engaging features, and the option of being anonymous. However, students preferred the apps based on established psychological frameworks with strong empirical evidence and the availability of remote mental health professionals with relevant qualifications and training. The main barriers to using MHapps identified by students included difficulties in differentiating between real and fake MHapps, lack of progress tracking of the users due to minimal human interactions, and ethical and data privacy concerns. Students also emphasized the cultural relevance of MHapps. The interpretation of our findings indicates that students demanded transparency regarding the authenticity of MHapps. Conclusion The findings of this exploratory investigation offer a better understanding of how college students perceive the usage of MHapps to improve resilience. This study highlights that further research should explore the specific needs and preferences of university students for developing and implementing effective MHapps for different contexts.